Temperate Agroforestry Systems - Gordon, Andrew (CAB International, 2018)
The 2nd edition of this book brings together many examples of temperate agroforestry and will make valuable reading for all those working in this area as researchers, practitioners and policy makers. The book is also of importance to students and teachers of agriculture, ecology, environmental studies and forestry in temperate regions.